Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12092610
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gut Microbiome Composition between Senior Orienteering Athletes and Community-Dwelling Older Adults

Abstract: Background: Gastrointestinal (GI) health is an important aspect of general health. Gastrointestinal symptoms are of specific importance for the elderly, an increasing group globally. Hence, promoting the elderly’s health and especially gastrointestinal health is important. Gut microbiota can influence gastrointestinal health by modulation of the immune system and the gut–brain axis. Diverse gut microbiota have been shown to be beneficial; however, for the elderly, the gut microbiota is often less diverse. Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…In line with the finding in professional athletes [106], the peak oxygen uptake was positively correlated with α-diversity indices also in older adults who were included in a randomized cross-over trial but there was no difference in α-diversity between the exercise and the control period [108]. Additionally, other studies in older adults did not detect differences in the α-diversity by the physical activity level of the participants [109][110][111][112] (Table 1). It has been suggested that the biological age and not the chronological age is mainly associated with a lower gut microbiota diversity [10], which may be one reason why several studies failed to show an association of the physical activity level and the α-diversity of the microbiota in older adults.…”
Section: Association With α-Diversity Indicessupporting
confidence: 80%
See 3 more Smart Citations
“…In line with the finding in professional athletes [106], the peak oxygen uptake was positively correlated with α-diversity indices also in older adults who were included in a randomized cross-over trial but there was no difference in α-diversity between the exercise and the control period [108]. Additionally, other studies in older adults did not detect differences in the α-diversity by the physical activity level of the participants [109][110][111][112] (Table 1). It has been suggested that the biological age and not the chronological age is mainly associated with a lower gut microbiota diversity [10], which may be one reason why several studies failed to show an association of the physical activity level and the α-diversity of the microbiota in older adults.…”
Section: Association With α-Diversity Indicessupporting
confidence: 80%
“…In Japanese communitydwelling older adults, only Bacillaceae and Fusobacteriaceae families were slightly different between the groups with low or high physical activity levels [109]. Two North-European studies compared community-dwelling older adults with high or low physical activity [110] or fitness levels [117]. Fart et al [110] compared the gut microbiota between communitydwelling older adults and physically active senior orienteering athletes in Sweden.…”
Section: Association With the Gut Microbiota Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings from the American Gut Project revealed that chronic exercise training benefits older adults by maintaining the stability of the gut microbiota (microbial composition and function) induced by aging [ 277 ]. Recent data demonstrated that masters athletes can be seen as a model of healthy aging also from the perspective of the microbiota [ 278 ]. Compared to community-dwelling older adults, senior orienteering athletes displayed a more homogeneous composition of gut microbiota, with higher levels of F. prausnitzii that is associated with positive health benefits, such as good gastrointestinal health, as well as psychological well-being that is most likely due to changes in the gut–brain axis [ 279 ].…”
Section: Nutritional Considerations For Masters Athletesmentioning
confidence: 99%